1986
DOI: 10.1113/jphysiol.1986.sp016219
|View full text |Cite
|
Sign up to set email alerts
|

Passive transport and binding of lead by human red blood cells.

Abstract: The uptake of Pb into human red blood cells has been studied using Pb buffers. Passive Pb movements can be studied conveniently when the cells are depleted of adenosine 5'‐triphosphate (ATP), to eliminate active transport, and of inorganic phosphate, to prevent precipitation of lead phosphate. Pb can cross the membrane passively in either direction. Influx and efflux show similar properties. Passive Pb transport is strongly stimulated by HCO3‐, and is reduced by replacing Cl‐ with ClO4‐. It is inhibited by low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 15 publications
2
37
0
2
Order By: Relevance
“…It was suggested that anionic complexes formed between copper and anions (especially chloride) were transported as surrogate substrates by the anion exchange system (1). Such a mechanism has also been reported for the uptake of lead (38,39), zinc (23), and cadmium (30) in human red blood cells. This suggests that these anion transporters may play a hitherto unexpected role in metal homeostasis in humans (see below).…”
Section: Discussionmentioning
confidence: 92%
“…It was suggested that anionic complexes formed between copper and anions (especially chloride) were transported as surrogate substrates by the anion exchange system (1). Such a mechanism has also been reported for the uptake of lead (38,39), zinc (23), and cadmium (30) in human red blood cells. This suggests that these anion transporters may play a hitherto unexpected role in metal homeostasis in humans (see below).…”
Section: Discussionmentioning
confidence: 92%
“…Baghurst et al 1987Baghurst et al , 1992Baghurst et al , 1995McMichael et al 1988McMichael et al , 1994Tong et al 1996Rothenberg et al 1989Schnaas et al 2000Factor-Litvak et al 1991Wasserman et al 1992Bellinger et al 1984, 1985a, 1986b, 19889a, 1989b Coscia et al 2003;Dietrich et al 1986Dietrich et al , 1987aDietrich et al , 1987bDietrich et al , 1991Dietrich et al , 1993aDietrich et al , 1993bRis et al 2004 development at age 6. 389 Children born to urban disadvantaged women in Cleveland, Ohio followed from birth to 7 years old.…”
Section: Health Effectsmentioning
confidence: 99%
“…Although the mechanisms by which lead crosses cell membranes have not been fully elucidated, results of studies in intact red blood cells and red blood cell ghosts indicate that there are two, and possibly three, pathways for facilitated transfer of lead across the red cell membrane. The major proposed pathway is an anion exchanger that is dependent upon HCO 3 -and is blocked by anion exchange inhibitors (Bannon et al 2000, Simons 1985, 1986a, 1986b. A second minor pathway, which does not exhibit HCO 3 -dependence and is not sensitive to anion exchange inhibitors, may also exist (Simons 1986b).…”
Section: Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Pb 2+ ions enter erythrocytes, they mainly bind to hemoglobin, with an estimated ratio in the cytosolic environment of bound to free lead of 6000:1. Binding with hemoglobin is not influenced by the oxygenation state [6]. Pb 2+ is transported across the cell membrane via a number of mechanisms, but in erythrocytes Pb 2+ transport is mediated by the anion exchanger Cl -/HCO 3 -, band 3 protein, and the Ca-ATP pump.…”
Section: Introductionmentioning
confidence: 99%